The Mediating Role of Organizational Commitment: A Supply Chain Management for Examining the Effect of Quality of Work Life and Job Satisfaction on Employee Performance - Arifin, A Hadi; Raza, Hendra; Saputra, Jumadil; Puteh, Anwar; Sofyan, Sofyan (International Journal of Supply Chain Management, 2020)
This study aims to examine the effect of quality of work-life and job satisfaction on employee performance with organizational commitment as a mediating variable In the Health Office of The North Aceh District. The sample in this study was 120 respondents. Data analysis using the AMOS SEM program. The results of data analysis, quality of work-life and job satisfaction have an influence on organizational commitment, and job satisfaction has a significant effect on employee performance. The quality of work-life and organizational commitment does not affect employee performance. Organizational commitment cannot mediate the relationship between quality of work-life and job satisfaction with employee performance. The results of the study recommend encouraging employee performance, work skills and policies for organizational commitment. It should be noted that the work environment of employees and also job satisfaction is maintained with colleagues and superiors, so that employee performance is better in the future.